Georgia : Sixth Review Under the Extended Arrangement and Requests for a Waiver of Nonobservance of Performance Criterion, Modification of Performance Criteria, and Augmentation of Access-Press Release; Staff Report; and Statement by the Executive Director for Georgia. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2020)
This paper discusses Georgia's Sixth Review Under the Extended Arrangement and Requests for a Waiver of Nonobservance of Performance Criterion, Modification of Performance Criteria, and Augmentation of Access. The coronavirus disease 2019 (COVID-19) pandemic has hit the Georgian economy hard. A drop in external demand and tourism has widened the current account deficit, led to a depreciation of the exchange rate, and a substantial decline in economic activity. The authorities have acted rapidly by introducing sweeping containment measures and targeted support to households and to most affected sectors. The National Bank of Georgia has appropriately maintained a moderately tight monetary policy stance, while allowing exchange rate to remain flexible. Monetary policy decisions should be based on close monitoring of inflationary expectations. Advancing structural reforms would help sustain medium-term growth potential and achieve a faster recovery after the pandemic. Adopting the indexation rule for public pension would contribute to sustain the income of pensioners. Completing the banking resolution framework and implementing the insolvency framework would help support the recovery. The augmentation of access under the Extended Fund Facility arrangement should support the authorities' policies to address the COVID-19 shock and help meet the urgent balance-of payments need.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet